Direct Evidence of Subsurface Oxygen Formation in Oxide‐Derived Cu by X‐ray Photoelectron Spectroscopy. (10th December 2021) - Wang, Hsin‐Yi; Soldemo, Markus; Degerman, David; Lömker, Patrick; Schlueter, Christoph; Nilsson, Anders; Amann, Peter
Abstract: Subsurface oxygen has been proposed to be crucial in oxide‐derived copper (OD‐Cu) electrocatalysts for enhancing the binding of CO intermediates during CO2 reduction reaction (CO2 RR). However, the presence of such oxygen species under reductive conditions still remains debated. In this work, the existence of subsurface oxygen is validated by grazing incident hard X‐ray photoelectron spectroscopy, where OD‐Cu was prepared by reduction of Cu oxide with H2 without exposing to air. The results suggest two types of subsurface oxygen embedded between the fully reduced metallic surface and the Cu2 O buried beneath: (i) oxygen staying at lattice defects and/or vacancies in the surface‐most region and (ii) interstitial oxygen intercalated in metal structure. This study adds convincing support to the presence of subsurface oxygen in OD‐Cu, which previously has been suggested to play an important role to mitigate the σ‐repulsion of Cu for CO intermediates in CO2 RR. Abstract : Subsurface oxygen has been proposed to be crucial for oxide‐derived copper (OD‐Cu) in electrochemical CO2 reduction. In this work, a high‐resolution spectral feature of subsurface oxygen in OD‐Cu was observed by in situ grazing incident hard X‐ray photoelectron spectroscopy. Two types of subsurface oxygen were identified: oxygen staying at lattice defects (in green) and interstitial oxygen intercalated in metal structure (in blue).